1997
DOI: 10.1007/s004410050941
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic differentiation: the role of agrin in the formation and maintenance of the neuromuscular junction

Abstract: Abstract. Upon arrival of a motor axon at the muscle fiber, signals released from its growth cone initiate the formation of a synapse. This process consists of two stages: arrest of axon growth at the target area and differentiation of pre-and postsynaptic cells at the site of nerve-muscle contact. Studies of regenerating neuromuscular junctions in vertebrates have revealed that important signals for the formation of this synapse are located in the synaptic basal lamina, and attempts to identify these signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 107 publications
1
7
0
1
Order By: Relevance
“…Particularly interesting is the reduced laminin-binding capability of miniagrin after MMP-12 processing. Denzer and coworkers have shown that the NtA domain alters the size of induced AChR clusters but not the overall extent of the induction [33]. AChR aggregates induced by full-length agrin are more than twofold smaller than those induced by a fragment without the NtA domain (equivalent to cleavage products A–C).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly interesting is the reduced laminin-binding capability of miniagrin after MMP-12 processing. Denzer and coworkers have shown that the NtA domain alters the size of induced AChR clusters but not the overall extent of the induction [33]. AChR aggregates induced by full-length agrin are more than twofold smaller than those induced by a fragment without the NtA domain (equivalent to cleavage products A–C).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction with dithiothreitol (DTT) showed that the observed mass corresponds to the calculated mass of C6, however, no precise measurement for fragment C5 could be obtained, which is attributable to incomplete cleavage by CNBr that resulted in a fragment of C3‐C4‐C5. Heterogeneous N ‐glycosylation on C3 might explain the lack of a well‐defined mass spectrum of the C3‐C4‐C5 fragment 6, 7. However, cleavage of NtA‐FS by CNBr followed by reduction demonstrates that C5 is linked via disulfide bridges to C6.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, NtA is a target of alternative mRNA splicing that causes an insert of seven amino acid residues 4, 5. The NtA domain is followed by nine repeats of follistatin‐like (FS) domains 6, 7. Mapping of the laminin‐binding site of NtA revealed that two amino acid residues are critical for binding 8.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is important to note that a lot of evidence in recent years suggested that multiple cellular interactions between the pre‐ and postsyanptic elements, involving some local controls (via agrin, neuregulin, etc. ), are necessary for synaptic reformation of the regenerating SCs, axons, and AChR sites in NMJs ( Kleiman and Reichardt, 1996 ; Denzer et al, 1997 ; Burden, 1998 ) . This study does not address the possibility that the observed changes may provide direct and distinct proof for the synaptic interactions.…”
Section: Discussionmentioning
confidence: 99%